Protest technologies and media revolutions : the longue durée - Karatzogianni, Athina; Schandorf, Michael; Ferra, Ioanna (Bingley, U.K. : Emerald Publishing Limited, 2020)
Contains an Open Access chapter. Protest Technologies and Media Revolutions portrays the critical role of mass connection in the success of any movement, resurrection, protest, and revolution. The communication mechanisms for this connection have, at times, evolved and elsewhere undergone revolutions of their own. Authors debate this relationship, and the strategies and lessons of 'connecting to the masses' considering the development of media, technology and communication strategies over the last century. Key topics covered include revolution, communication, protest and technology, spanning from the Russian Revolution to the present day. The discussion is not limited to historic cases of technology and revolution, nor to contemporary ones. The book, therefore, generates a debate about how art, media and communication technologies have been operationalized to connect, mobilize and organize, in different historical times, and in diverse national, political, and socio-economic contexts.
Chapter 1. Introduction: Protest Technologies and Media Revolutions in the Longue Durée; Athina Karatzogianni, Ioanna Ferra, and Michael Schandorf -- Part I: From the Russian Revolution to Post-Soviet Digital Activism and the New Cold War -- Chapter 2. Art as a Form of Social Action in the Russian Avant-garde (1905-1930); Maria Tsantsanoglou -- Chapter 3. Secret Police and Public Sphere. The East German State Security Service ('Stasi') between Media Control and Public Relations; Sebastian Haller -- Chapter 4. The Russian Dream and Victor Pelevin's Generation "Π": Ideology in pPost-Soviet Russia; Angelos Theocharis -- Chapter 5. Soviet Communicative Control: Some Implications on Digital Activism in Contemporary Russia; Ilya Kiriya -- Chapter 6. A Comparative Cyberconflict Analysis of Digital Activism Across Post-Soviet Countries; Athina Karatzogianni, Galina Miazhevich, and Anastasia Denisova -- Chapter 7. Dis/engagement in Post-Soviet Communicative Ecologies: Re-framing the 'Chinatown' Dissent Campaign in Belarus; Galina Miazhevich -- Chapter 8. Media in Tooth and Claw: Ecologies of Post-truth Suasion in Total (Culture) War; Michael Schandorf Part II: The Road to Occupy and its Influence -- Chapter 9. Creating the collective: Social Media, the Occupy Movement and its Constitution as a Collective Actor Anastasia Kavada -- Chapter 10. Ground the Drones: Direct Action and Media Activism; Kevin Howley -- Chapter 11. Beyond Social Media Determinism? How Artists Reshape the Organization of Social Movements Alberto Cossu OPEN ACCESS -- Chapter 12. The City is a Work of Art and Everyone is an Artist": Collaborative Protest Art, Participation and Space Reproduction at the 2014 Hong Kong's Umbrella Movement.; Georgios Patsiaouras. -- Chapter 13. A Comparative Study of the Delhi Nirbhaya Protests and the Occupy Nigeria Movement: Evaluating Uses of ICTs and Social Media; Adrija Dey and Shola Olabode -- Chapter 14. From Classical Syndicalism to Spain's 15-M Movement; Cristina Flesher Fominaya -- Chapter 15. The Trials and Tribulations of Social Media and Transnational Labour Solidarity; Torsten Geelan and Andy Hodder -- Chapter 16. The Online Communication Strategies of a Small-scale Social movement: The Case of the Greek 'Do Not Pay' Social Movement; Stamatis Poulakidakos, Anastasia Veneti, and Maria Rovisco -- Chapter 17. The EU Referendums in the Twittersphere: #Grexit, #Brexit and the #Catalanreferendum; Ioanna Ferra and Dennis Nguyen -- Chapter 18. The Geeks of the Squares: Agency, Control and Surveillance in Protest Movement Mediation Technologies; Athina Karatzogianni and Michael Schandorf.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Communication -- Social aspects; Social Science -- Sociology -- General; Social interaction